Legal Systems in North African Countries Reviewed from the Perspective of Problems and Solutions - Steven Ng’ang’a (IJOLARES: Indonesian Journal of Law Research, 2025)
The legal system in every country has a very important position and function. However, it should be noted that each country has a different legal system. Likewise, the legal system in North African countries has a different legal system from other countries in the world. The legal system in North African countries is indeed very interesting to study. The purpose of this research is to examine the legal system in North African countries from the perspective of problems and solutions. The unique combination of Islamic legal traditions, colonial heritage, and local customs creates a complex and dynamic legal system. Literature review is the method used by researchers to uncover the legal system in North African countries. Through analysis of the data obtained, the results of this study were able to show that the legal system in North African countries has unique characteristics, influenced by a long history of colonialism, Islamic influence, and local customs. Some common problems faced by the legal system in North African countries are (1) Legal dualism which is a challenge in itself in legal development; (2) Corruption is a serious problem that hinders law enforcement and weakens public trust in the justice system; (3) Women and minority groups often experience discrimination in access to justice. To overcome these problems, many countries in North Africa have made legal reform efforts, including (1) Legal harmonization is a strategic effort to overcome the complex problem of legal dualism in North African countries; (2) Strengthening judicial institutions is indeed one of the keys to overcoming the various complex problems faced by the legal system in North African countries; (3) Criminal law reform is a crucial step in overcoming the complex problems of the legal system in North African countries.